2019
DOI: 10.1152/ajpendo.00173.2019
|View full text |Cite
|
Sign up to set email alerts
|

Fetal androgen signaling defects affect pancreatic β-cell mass and function, leading to glucose intolerance in high-fat diet-fed male rats

Abstract: We previously demonstrated that androgen signaling expands pancreatic β-cell mass in the sexual maturation period ( Am J Physiol Endocrinol Metab 314: E274–E286, 2018). The aim of this study was to elucidate whether fetal androgen signaling plays important roles in β-cell mass development and β-cell function in adulthood, defects of which are associated with type 2 diabetes mellitus. In the pancreas of male fetuses, androgen receptor (AR) was strongly expressed in the cytoplasm and at the cell membrane of Nkx6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Fetal androgen not only acts to promote the development of reproductive organs such as internal and external genitalia but also acts on the development of non-reproductive organs such as pancreatic βcells in males. 2,3 A transient testosterone surge in neonates is responsible for brain masculinization. 1 Additionally, an increase in testosterone during puberty contributes to the development of secondary sexual characteristics in males.…”
mentioning
confidence: 99%
“…Fetal androgen not only acts to promote the development of reproductive organs such as internal and external genitalia but also acts on the development of non-reproductive organs such as pancreatic βcells in males. 2,3 A transient testosterone surge in neonates is responsible for brain masculinization. 1 Additionally, an increase in testosterone during puberty contributes to the development of secondary sexual characteristics in males.…”
mentioning
confidence: 99%
“…Previous studies have shown that the activity of the androgen receptor can regulate insulin secretion from islet beta‐cells in rats and mice (Harada et al., 2018, 2019; Kooptiwut et al., 2015; Li et al., 2008; Xu et al., 2017). There seems to be an overall protective effect in rat islet cells exposed to testosterone via attenuation of superoxide production and decreased Caspase 3 cleavage under a high‐glucose environment (Kooptiwut et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If so and based on previous findings by others showing that testosterone increases insulin secretion (More, Mishra, Hankins, et al., 2016; Morimoto et al., 2001, 2005; Ramaswamy et al., 2016), we thought it possible that flutamide, an AR antagonist, would attenuate the plasma insulin in response to separation and hypoxia and possibly improve insulin sensitivity. Furthermore, we might expect reciprocal changes in plasma glucose due to the flutamide‐mediated modulation of pancreatic islet cell activity (Harada et al., 2019; Kupreeva et al., 2019). Or, it could be possible that corticosterone‐driven insulin resistance (Dallman et al., 1995; Jimeno et al., 2018; Morakinyo et al., 2019; Strack et al., 1995; Tadaishi et al., 2018) could increase plasma glucose which would then stimulate the release in insulin, and that this could be modulated by AR blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations